Pengaruh Level Rendaman Ekstrak Kulit Manggis (Garcia Mangostana L ) dan Daya Simpan terhadap Kualitas Fisik Telur Ayam Ras - Muhamad Zidni Nuro; Roisu Eny Mudawaroch; Faruq Iskandar (Jurnal Riset Agribisnis dan Peternakan, 2022)
This study aims to determine the potential of mangosteen peel extract (Garcia Mangostana L) as an egg preservative to improve the physical quality of broiler eggs soaked for 6 weeks. This study used 105 chicken eggs, soaked for 24 hours and stored for 6 weeks. Methods Using Completely Randomized Design (CRD) with 4 treatments and 3 replications. The parameters taken are egg white index value, egg yolk index value, egg yolk color, pH value of egg white and yolk. The results showed that mangosteen peel extract had a significant effect (P<0.01) on the egg white index with values ​​of 0.152, 0.89, 0.81, 0.83, 0.80, 0.56, 0.29. The yolk index value had a significant effect (P<0.01) of 0.41, 0.34, 0.32, 0.28, 0.22, 0.14, 0.09. The yolk color value had a significant effect (P<0.01) of 13.00, 12.67, 12.33, 1175, 11.08, 9.17, 8.08. The pH value of egg white had a significant effect (P<0.01) of 7.79, 7.95, 8.11, 8.57, 8.91, 9.47, 9.78. The egg yolk pH value had a significant effect (P<0.01) of 6.20, 6.27, 6.46, 6.56, 6.65, 6.75, 6.82. The Haugh unit egg had a significant effect (P<0.01) of 115.6, 98.5, 93.6, 94.8, 94.3, 83.7, 69.8. The addition of the concentration of mangosteen rind extract up to 10% can maintain egg quality, in terms of the index value of egg white, egg yolk, egg pH, egg yolk color and Haugh Unit value.